(untitled) (The Pretoria Student Law Review, 2021)
The freedom or the right to engage in peaceful protest is one that can be perceived to have been enshrined, and guaranteed, under the right to freedom of expression while also being closely linked to the right to freedom of association and freedom of speech. This right is a core feature and foundation of a democratic society as it ensures that the people’s representatives can be interrogated in the people’s court for any act not in conformity with the wishes of the people. Civil society groups are usually at the forefront of many protests — serving as the rallying point and the report by the Office of the High Commissioner for Human Rights (OHCHR) recently recognised this, stating that civil society plays a crucial role in the realisation of human rights on the ground. Unfortunately, most governments around the world feel threatened once faced with a group of people demanding accountability from government on specific issues. Their default response almost always is to shut down protests by resorting to the use of force and other violent means. The civil society space is being eliminated by governments even as they continue to face threats, bans on peaceful demonstrations, confiscation of computers, imprisonments and even killings. This unfortunate reality was described by CIVICUS: Democratic South Africa’s National Assembly passed the so called “secrecy bill”, which places hurdles against CSOs and journalists obtaining information to expose official wrongdoing, despite fierce civil society resistance. Such laws are brought in and applied under a number of guises. Commonly, rhetoric around national security and controlling terrorist activities was used to justify new restrictions on fundamental freedoms in the years following the 9/11 terrorist attacks in 2001. Nigeria is not an exception to this unacceptable trend and this paper will look at how the use of force in Nigeria has become one of the biggest impediments to peaceful protests and has in some instances, resulted in fatalities